Kinetics of deposition and clearance of inhaled mineral dusts during chronic exposure. Issue 10 (October 1985) - Vincent, J H; Johnston, A M; Jones, A D; Bolton, R E; Addison, J
Abstract : New inhalation studies have been carried out with rats exposed to UICC (Union International Contre le Cancer) amosite asbestos, with the main aim of further elucidating the factors the influence the accumulation of dust in the lung during prolonged chronic exposure. The results show that, for exposure times beyond a few weeks, the lung burden rises linearly and does not level off as predicted by simple models based on ideas taken from the 1966 report of the Task Group on Lung Dynamics. Furthermore, the lung burden is found to scale directly in proportion to the exposure concentration in a way that seems to contradict the overload hypothesis stated earlier. Nevertheless, the general pattern exhibited by our results for asbestos is markedly similar to that found elsewhere for rats inhaling diesel fume, leading to the suggestion that it is general (and not specific to fibrous dust); and the hypothesis that, whereas overload of clearance can take place at high lung burdens after exposure has ceased, it is cancelled by the sustained stimulus to clearance mechanisms provided by the continuous challenge of chronic exposure. The linearity of the increase in lung burden is explained in terms of a kinetic model involving sequestration of some inhaled material to parts of the lung where it is difficult to clear. The particular sequestration model favoured is one where, the longer a particle remains in the lung without being cleared, the more likely it will be sequestrated (and therefore less likely cleared). It is believed that such ideas may eventually be useful in forming exposure-dose relations for epidemiology.